1. CLINICAL FEATURES AND IMAGES OF COMPLICATIONS OF PNEUMONIA IN CHILDREN AT PHUONG CHILDREN'S HOSPITAL FROM JANUARY 2022 TO JANUARY 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the clinical characteristics and imaging of complications of pneumonia in children.Subjects and methods: Cross-sectional study of 123 children ≤ 16 years old diagnosed with complicated pneumonia by computed tomography.Results: The average age of the patients was 51.43 ± 37.48 months old, with the majority under 5 years old. No significant sex differences were noted. The most frequently identified pathogen was Streptococcus pneumoniae (34.1%). The most common clinical symptoms were fever (97.5%) and poor feeding/refusal to eat or breastfeed (89.4%), suggesting systemic involvement. The predominant physical sign reflecting the degree of lung injury and respiratory compromise was tachypnea (99.2%). Altered consciousness was observed in 46.3% of patients. Laboratory findings showed elevated white blood cell counts and C-reactive protein levels, with higher values indicating more complicated disease progression. Anemia (decreased hemoglobin) was present in 79.7% of cases, mostly among patients with severe illness and multiple concurrent complications. 72.4% positive for bacterial culture. Common complication is pleural effusion (71.5%), primarily affecting the right lung and most often involving the pulmonary lobes. Chest X-ray findings predominantly showed mixed lesions (consolidation plus nodular opacities), accounting for 58.5%. On CT, consolidation was present in 57.7%, with well-defined margins in the majority (92.7%). Pleural effusion was the most frequent CT finding, detected in 76.4% of cases. For complicated pneumonia in children, medical treatment is still the main method (61.8%).Conclusion: Complicated pneumonia in children is a severe condition with ready and diverse manifestations.
Keywords: Pneumonia with evidence in children; severe pneumonia; lung abscess.